Langke Bulawa Statue in the perspective of review Bada valley site culture - Setyawan, Alfan; Yudhanto, Sigied Himawan (Institut Seni Indonesia Surakarta, 2024)
This article proposes a model of interpretation of the Langke Bulawa statue based on a theoretical approach based on the cultural sociology theory of naturalism from the perspective of the place and location where the statue is located, namely in the Bada Valley. Cultural sociology can fill the cultural gap in the sociology of art and can provide a method for identifying the linguistic context that surrounds social institutions. The aim is to discuss classical readings of the object by constructing alternatives that do not attempt to decipher symbolic content or show naturalistic representations in the form of sculptural objects. Instead, in Langke Bulawa Statue, the author proposes a theoretical approach that goes beyond the descriptive approach that ultimately provides only a vague interpretation of the Langke Bulawa statue as stelae by considering the statue as an artistic expression of a people with aesthetic norms, conditioned by traditions, resulting in a kind of object form that must try to be found based on the representation of cultural views in Bada Valley, where the physical boundaries between humans and non-humans disappear, to show figures that have the same essence, but merge in one object form, namely the Langke Bulawa statue as a representation of a figure with the only female form where the implications of a sociocultural perspective in this study will contribute to interpreting the Langke Bulawa statue as a potential contribution of cultural sociology research related to megalithic relics in Central Sulawesi Province.